The Role of the Issuer in Loss of Electronic Money Users in the Failure of the Balance Refillment Process From the Consumer Protection Perspective - Zhazha Aulia Thermalista; Dwi Desi Yayi Tarin (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Electronic money services are an innovation from the publishers in terms of following world developments towards non-cash payments. Electronic money is referred to as a prepaid payment service which is different from debit and credit cards by not requiring a Personal Identification Number (PIN) so that the relationship between the user and the issuer is only limited to parties in buying and selling transactions. It is undeniable that there are several things that can harm consumers, such as failures during transactions to replenish electronic money balances but the funds owned by the user have been sent or have been deducted. So in this case the law regarding the payment service sector, especially electronic money and consumer protection is needed. The research this time aims to show the validity of the law in Indonesia regarding the rules for the implementation of refilling electronic money balances which are regulated in Bank Indonesia Regulation Number 20/6/2018/PBI concerning Electronic Money. Then the role of the issuer in the context of the loss of electronic money users when there is a failure in the balance refill process from the perspective of consumer protection, which of course still requires review considering that there are still problems with failed electronic money balance replenishment transactions. The research was conducted using a normative juridical method that is descriptive-analytical and uses a statutory approach.